Black History Month Programs: Performance and Heritage - Addison, Wanda (Material Culture Review)

(untitled) (Cape Breton University Press, 2015)
Abstract Implications embedded in Black History Month programs access desires for cultural recognition of African American contributions and history within the United States. Equally important at these events is the implicit furthering of knowledge and connection to the past and the sustainability of African American heritage and culture. Concepts of “home” as historical, national, and individual community, infuse each performance and support and encourage connections that in turn insist on the removal of myopic considerations of cultural subjectivity and sustainability. Black History Month programs revision “home” through counter-stories of Blackness in America and American-ness in Black America.